Efektivitas Penggunaan Infrared pada Pijat Oksitosin dalam Upaya Memperbanyak Produksi ASI - Wiwik Puspita Dewi; Sri Haryanti, Rusiana; Nugroho, Eko (Profesi (Profesional Islam) : Media Publikasi Penelitian, 2025)
Breast milk is the main source of nutrients for babies that has extraordinary benefits for their growth and development. However, not all breastfeeding mothers can produce optimal amounts of breast milk, so effective methods are needed to increase their production. This study aims to examine the effectiveness of the use of infrared in oxytocin massage in increasing breast milk production in breastfeeding mothers. The design of this study uses pre-experimental with a one-group pretest-posttest design. The research was carried out at the Midwife's Independent Practice (PMB) in the Soloraya work area for 4 months. The study population is all breastfeeding mothers who are in the work area of the Solo Raya City Health Office, with samples of breastfeeding mothers on days 1 to 7 who experienced breast milk production disorders. The sampling technique was carried out using simple random sampling, with instruments in the form of a checklist to monitor breast milk production and the use of oxytocin and infrared massage kits.